Development and evaluation of an antimicrobial urinary catheter - Fisher, Leanne (2011)
Over the past few years the healthcare setting has seen a vast increase in the use of medical devices and whilst this may have improved clinical outcomes for patients their increase in use has given rise to an increase in medical - device associated infections. It has been reported that urinary tract infections (UTIs) account for up to 40% of all healthcare associated infections and about 80% of those are associated with catheter use [1]. Urinary catheters are hollow, flexible, tubular devices designed to drain urine when inserted into a patient‟s bladder. They are widely used both on patients requiring short - term urinary catheterisation e.g. during and after some types of surgical procedures or long - term urinary catheterisation e.g. due to urinary incontinence. For patients undergoing long - term indwelling urinary catheterisation (LTC) it is almost inevitable that their catheter will become colonised with bacteria and a biofilm (an accumulation of microorganisms and their extracellular products that form a functional, structured community on a surface) [2] develop which can result in a symptomatic or asymptomatic catheter associated urinary tract infection (CAUTI). Infections associated with biofilms are difficult to treat due to the bacteria within the biofilm being insusceptible to antibiotic treatment. Often to resolve the infection, removal and replacement of the catheter is required and antibiotic treatment if necessary. Certain patients may require their catheter to be changed frequently, often causing considerable distress and morbidity and giving rise to increased medical costs. Biomaterials used to produce long - term urinary catheters that are able to completely resist bacterial colonisation for significant periods, remain elusive. The development of antimicrobial urinary catheters has, however, shown some success in clinical trials but only in the short-term.